An Analysis Of Linguistic Form And Language Function Of The Caretakers Speech Found In The Miracle Worker Movie - Supriyati, Supriyati, Prof. Endang Fauziati, M.Hum, Dr. Dwi Haryanti, M.Hum (2015)
The objective of this study to describe the type of linguistics form and type of language function of the caretakers' speech found in the Miracle Worker movie. The type of this study is descriptive qualitative research. The data are utterance in the Miracle Worker movie. In collecting the data the writer uses documentation technique. The data are collected from the language used by the caretaker likes mother, father, servant, aunt, teacher, and brother. Firstly the data analyzed by Frank theory, (1972: 6) for classification the type of linguistics form focus on the word, phrase, and sentence. The result of the research shows that four types of word namely noun, verb, adjective, and adverb, on the phrase found three types of phrase there are noun phrase, verb phrase, and adverbial phrase, meanwhile in the sentence the researcher found two types classification of the sentence there are classification sentence by type consist of declarative sentence, interrogative sentences, exclamatory sentences, and imperative sentences, then classification sentence by number of full prediction consist of simple sentence and compound-complex sentence. Second the researcher classification type of language function on the utterance produced by caretaker by using M. A. K Halliday theories (1992: 11). The result of this research shows, there are six types of language functions they are instrumental function, heuristic function, regulatory function, representational function, interactional function, and personal function. The most dominant the type of language function used by caretaker in the Miracle Worker movie is regulatory function.